VISCERAL ADIPOSITY AS A GLOBAL FACTOR OF CARDIOVASCULAR RISK - G. A. Chumakova; T. Yu. Kuznetsova; M. A. Druzhilov; N. G. Veselovskaya (Российский кардиологический журнал, 2018)
Obesity becomes one of the main risk factors of development and progression of cardiovascular diseases. Association of the high values of body mass index with overall and cardiovascular mortality is confirmed by the results of meta-analyses of multiple prospective studies. On the other hand, the two most global problems of this relationship — “obesity paradox” and heterogeneity of obesity phenotypes by cardiometabolic risk, released multiple discussions on the issues of predictive value of body overweight and obesity, and worth of correction in patients under the secondary prevention framework. Nowadays, the fact became obvious that maximum role in the risk raise plays a specific type of adipous tissue, and morphological changes in visceral adipous tissue within the processess of remodeling and inflammation, with further dysfunction. In the article, an assessment provided of the ethiopathogenetic role of visceral adipous tissue in cardiovascular continuum; a review provided of the verification approaches to visceral obesity, and a strategy proposed for cardiovascular risk stratification in association with obesity, in a broad clinical framework.